2011
DOI: 10.2337/dc10-2424
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Quality of Life in Older Adults With Diabetes

Abstract: OBJECTIVETo evaluate associations between health-related quality of life (HRQL) and geriatric syndromes, diabetes complications, and hypoglycemia in older adults with diabetes.RESEARCH DESIGN AND METHODSA race-stratified random sample of 6,317 adults with type 2 or type 1 diabetes, aged 60 to 75 years, enrolled in Kaiser Permanente Northern California, who completed a survey that included a HRQL instrument based on the Short Form 8-item health survey. Administrative records were used to ascertain diagnoses of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
173
0
7

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 205 publications
(187 citation statements)
references
References 22 publications
7
173
0
7
Order By: Relevance
“…First, our study adds to literature by confirming that racially and ethnically diverse older women with diabetes are at high risk of urinary incontinence. 23 Combined with previous studies from the Diabetes and Aging Study, which showed a strong relationship between urinary incontinence and healthrelated quality of life, 24 our results reinforce the importance of asking about, diagnosing, and treating urinary incontinence in diverse older women with diabetes. 25 Second, for older women with diabetes and incontinence, improving glycemic control has often been advocated as a means of improving urinary incontinence symptoms.…”
Section: Discussionsupporting
confidence: 86%
“…First, our study adds to literature by confirming that racially and ethnically diverse older women with diabetes are at high risk of urinary incontinence. 23 Combined with previous studies from the Diabetes and Aging Study, which showed a strong relationship between urinary incontinence and healthrelated quality of life, 24 our results reinforce the importance of asking about, diagnosing, and treating urinary incontinence in diverse older women with diabetes. 25 Second, for older women with diabetes and incontinence, improving glycemic control has often been advocated as a means of improving urinary incontinence symptoms.…”
Section: Discussionsupporting
confidence: 86%
“…Coexisting chronic medical conditions such as hypertension, chronic kidney disease, heart failure, chronic lung disease, musculoskeletal conditions, cancer, and history of stroke require particular attention. These comorbidities can have profound impacts on functional status and quality of life 20,21 and affect insulin requirements and self-care abilities. Older adults with type 1 diabetes may require frequent adjustments in insulin dosing, especially during acute illnesses, to decrease the likelihood of …”
Section: Comorbid Medical Conditionsmentioning
confidence: 99%
“…Older adults may also have other medical comorbidities, functional disabilities, erratic food intake, and insufficient social support. Individuals with geriatric syndromes (i.e., chronic pain, urinary incontinence, polypharmacy, cognitive impairment, frequent falls, and depression) [20][21][22][23] face additional difficulties in performing self-management tasks and lower quality of life. Clinical, functional, and psychosocial factors that should be identified and addressed when developing treatment plans are listed in Table 1 and discussed below.…”
mentioning
confidence: 99%
“…Social difficulties may impair their quality of life and increase the risk of functional dependency (38). The patient's living situation must be considered, as it may affect diabetes management and support.…”
Section: Other Factors To Considermentioning
confidence: 99%
“…Those receiving palliative care (with or without hospice) may require an approach that emphasizes comfort and symptom management, while deemphasizing strict metabolic and blood pressure control. (38).…”
Section: Other Factors To Considermentioning
confidence: 99%